HUBUNGAN AKTIVITAS FISIK DAN KUALITAS HIDUP LANSIA PENDERITA DIABETES MELLITUS TIPE 2 (JURNAL KESEHATAN MERCUSUAR, 2020)
ABSTRACT               Diabetes mellitus is a non-communicable disease whose prevalence continues to increase in the world, both in developed and developing countries. Physical activity is also a major risk factor in triggering Diabetes Mellitus. This study aims to determine the relationship of physical activity with the quality of life of elderly people with type 2 diabetes mellitus. The research method used is descriptive analytic with cross sectional design. The sampling technique in this research is purposive sampling with 58 samples. The instrument used in this study was a GPAQ physical activity questionnaire and quality of life using a WHOQOL questionnaire. The statistical test used is the chi square test. The results showed the majority with low activity of 23 elderly (38.6%) and the quality of life of the majority of good elderly totaling 30 elderly (51.7%) obtained p value of 0.001